Recurrence of appendix tumor: case report and literature update - Sakin, Abdullah; Sönmez, Gülçin Miyase; Şengiz Erhan, Selma; Arıcı, Serdar; Geredeli, Çağlayan; Cihan, Şener (The European Research Journal, 2020)
Herein, we report a case of appendix adenocarcinoma who presented with a recurrence 8 years after the initial diagnosis. A 54-year-old male underwent appendectomy in 2009. The pathology revealed a 1.7 cm diameter low grade mucinous carcinoid tumor. Any additional treatment was not recommended for patient other than appendectomy. The patient was admitted with the symptoms of ileus at 8 years after surgery and then underwent to right hemicolectomy in 2017. On histopathological examination of the specimen revealed a Goblet cell adenocarcinoid tumor, arising from iliocecal valv with pericolorectal tissue invasion of 5 cm in diameter. Lymph-node metastases were found in 16 dissected lymph nodes. The patient was initiated to treat with combined capecitabine and oxaliplatin chemotherapy. There is no clear evidence to support the superiority of any particular chemotherapy regimen for adjuvant treatment of appendix tumors. In this regard more studies are needed to use combined regimens.